2013
DOI: 10.1534/genetics.113.154690
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Osmotolerant Yeast Zygosaccharomyces rouxii to an Osmotic Environment Through Copy Number Amplification of FLO11D

Abstract: Copy number variations (CNVs) contribute to the adaptation process in two possible ways. First, they may have a direct role, in which a certain number of copies often provide a selective advantage. Second, CNVs can also indirectly contribute to adaptation because a higher copy number increases the so-called "mutational target size." In this study, we show that the copy number amplification of FLO11D in the osmotolerant yeast Zygosaccharomyces rouxii promotes its further adaptation to a florformative environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Thus, these isolates might enter the plant environments and be recovered again. The C. tropicalis strain obtained from the stored concentrate exhibited genomic patterns different from the C. tropicalis strains isolated from the air and water, as some osmotolerant yeasts may be able to adapt to environmental stress through gene mutation (Watanabe and others ; Wei and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these isolates might enter the plant environments and be recovered again. The C. tropicalis strain obtained from the stored concentrate exhibited genomic patterns different from the C. tropicalis strains isolated from the air and water, as some osmotolerant yeasts may be able to adapt to environmental stress through gene mutation (Watanabe and others ; Wei and others ).…”
Section: Resultsmentioning
confidence: 99%
“…This means that 4 out of the 5 FLO genes present in S. cerevisiae [ 70 ] differed between strains . It is known that changes in sequence, copy number transcriptional level and other regulatory mechanisms of the FLO genes affect several of the adaptive mechanisms of the cells towards detrimental environmental factors including flocculation, biofilm formation and agar invasion [ 71 73 ]. In fact, previous studies have shown direct evidence of the role of FLO genes on the adaptation capacity of yeast cells to overcome temperature or lignocellulosic-derived inhibitors [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, extreme high sugar tolerance ability makes Z. rouxii an increasing threat to high sugary food industries (Dakal et al, 2014;Vermeulen et al, 2015). On the other hand, Z. rouxii also played a central role in the production of traditional fermented foods (such as soy sauce) (Watanabe et al, 2013). Extreme yeasts produce and accumulate large amounts of osmo-protective metabolites.…”
Section: Discussionmentioning
confidence: 99%